Evaluation of the short and long estrus synchronization protocol in inseminated sheep with frozen semen - Yan Pierr Manrique Quispe; Uri Harold Pérez Guerra; Julio Málaga Apaza; Wilbur Rubén Ayma Flores; Oscar Efrain Cardenas Minaya; Manuel Guido Pérez Durand (Journal of the Selva Andina Animal Science)
The objective of the study was to evaluate the effect of short (5 days) and long (9 days) SC protocols in ewes inseminated with frozen semen on the diameter of the uterine horn and pregnancy rate. The experiment was carried out at the Carolina Experimental Center, belonging to the National University of the Altiplano, and 40 ewes between Corriedale and Criollas were used; in groups of 20 for each treatment, which were synchronized with intravaginal sponges based on Medroxyprogesterone acetate, for 9 days (long protocol) and 5 days (short protocol) and at the time of sponge removal, 350 IU of eCG were applied. To measure the diameter of the uterine horn, ultrasonography was performed at 36 h post sponge removal and at 56 h after cervical insemination with thawed semen and a subsequent ultrasonography at 35 days to confirm gestation. Quantitative data were analyzed using the statistical t-test for uterine horn diameter and Chi-square for gestation rate. The results for uterine horn diameter were 11.11±1.52 and 12.12±2.12 mm for the short and long synchronization protocol, respectively. Regarding the pregnancy rate, 21.05 % and 25 % were obtained for the short and long synchronization protocol, respectively. Therefore, we can conclude that the long progesterone treatment had better results than the short treatment both in uterine diameter and pregnancy rate, but this difference was not significant (p>0.05).